Modelling And Stress Analysis Of Lumbar Spine - Zulkifli, Siti Syazni (2015)

(untitled)
The lumbar spine modelling and analysis are crucial for prediction of the load impact and body movement in daily life activities. In this research, different load amount and moment are investigated. The analysis focuses on the high stress concentration since this area tends to get fractures. In order to predict the biomechanical response of lumbar vertebra, the three-dimensional finite element model of L1 to L5 included intervertebral disc was constructed by extracting the computed tomography scan data from Malaysian female. Analysis was performed under various loadings such as axial load, flexion, extension, lateral and torsion to determine the stress distribution and deformation on the model. The result shows that Maximum Von Mises Stress is lowest at vertebra L5, which is 1.37 MPa compared to vertebra L1 which is 4.29 MPa. Meanwhile, for the maximum displacement, vertebra L5 also lower compared to vertebra L1 which is 0.31 x 10-5 mm and 1.51 x 10-5mm respectively. The pedicle region is the areas that are subjected to the greatest stresses and which are more likely to be susceptible to degenerative diseases and injuries are identified. The analysis also was performed on the whole lumbar vertebra and the result shows that the Von Mises stress was highest under lateral moment and lowest under torsion moment. Based on the degree of rotation, it shows that the lumbar spine most flexible under flexion moment and less flexible under torsion moment.